Aging Well in Management Education: An Interview. (April 2023) - Risavy, Stephen D.; Deszca, Gene
With an unprecedently aging population and the abolition of mandatory retirement in many countries, management educators are remaining in their jobs longer than ever before; thus, it has never been more important to ask the question of: how can management educators remain effective and engaged while avoiding burnout throughout a career in the academy? The issue of aging well in management education is relatively under-acknowledged in the literature and we sought to move this topic into focus for higher education institutions and management educators. The interview we present focuses on the experiences of an accomplished management scholar and educator: Professor Emeritus and Full Professor, Gene Deszca. Dr. Deszca aged well as a management educator during his 37-year career at his institution until his retirement at the age of 69 and a half. The major themes from the interview suggest the benefits of interactions and relationships, autonomy, institutional support, and a willingness and ability to change. Based on these major themes, we provide implications for higher education institutions and management educators. It is our hope that management educators will engage with this interview and reflect on their own experiences while considering how they can age well throughout their career in the academy.